Neutralizing antibodies against SARS-CoV-2 are higher but decline faster in mRNA vaccinees compared to individuals with natural infection - Haissam Abou-Saleh (497840) (2022)
Background Waning protection against emerging SARS-CoV-2 variants by pre-existing antibodies elicited because of current vaccination or natural infection is a global concern. Whether this is due to the waning of immunity to SARS-COV-2 remains unclear. Aim We aimed to investigate the dynamics of antibody isotype responses amongst vaccinated naïve (VN) and naturally infected (NI) individuals. Methods We followed up antibody levels in COVID-19 messenger RNA (mRNA)-vaccinated subjects without prior infection (VN, n = 100) in two phases: phase-I (P-I) at ~ 1.4 and phase-II (P-II) at ~ 5.3 months. Antibody levels were compared with those of unvaccinated and naturally infected subjects (NI, n = 40) at ~ 1.7 (P-1) and 5.2 (P-II) months post-infection. Neutralizing antibodies (NTAb), anti-S-RBD-IgG, -IgM and anti-S-IgA isotypes were measured. Results The VN group elicited significantly greater antibody responses (P < 0.001) than the NI group at P-I, except for IgM. In the VN group, a significant waning in antibody response was observed in all isotypes. There was about an ~ 4-fold decline in NTAb levels (P < 0.001), anti-S-RBD-IgG (~5-fold, P < 0.001), anti-S-RBD-IgM (~6-fold, P < 0.001) and anti-S1-IgA (2-fold, P < 0.001). In the NI group, a significant but less steady decline was notable in S-RBD-IgM (~2-fold, P < 0.001), and a much smaller but significant difference in NTAb (<2-fold, P < 0.001) anti-S-RBD IgG (<2-fold, P = 0.005). Unlike the VN group, the NI group mounted a lasting anti-S1-IgA response with no significant decline. Anti-S1-IgA, which were ~ 3-fold higher in VN subjects compared with NI in P-1 (P < 0.001), dropped to almost the same levels, with no significant difference observed between the two groups in P-II. Conclusion Whereas double-dose mRNA vaccination boosted antibody levels, vaccinated individuals’ ‘boost’ was relatively short-lived. Other information Published in: Journal of Travel Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1093/jtm/taac130 Additional institutions affiliated with: WHO Collaborating Centre for Disease Epidemiology Analytics on HIV/AIDS, Sexually Transmitted Infections, and Viral Hepatitis - WCM-Q